Skeletal effects of the alteration of masseter muscle function - Mayne Robert J.; van der Poel Chris; Woods Michael G.; Lynch Gordon S. (Sciendo, 2015)
To investigate the effects of muscle denervation and the introduction of the β2-adrenoceptor agonist, formoterol, on the relationship between muscles and underlying skeletal growth.